Healthcare professionals' perceptions of malnutrition management and oral nutritional supplement prescribing in the community: A qualitative study. (August 2021) - Browne, Sarah; Kelly, Lucy; Geraghty, Aisling A.; Reynolds, Ciara ME.; McBean, Laura; McCallum, Kimberley; Clyne, Barbara; Bury, Gerard; Perrotta, Carla; Kennelly, Sharon; Bradley, Catriona; McCullagh, Laura; et al.
Summary: Background & aim: Protein-energy malnutrition is under-recognised in the community despite being common in older adults due to physiological and social changes which are often compounded by chronic disease. This qualitative study aimed to explore the opinions of healthcare professionals (HCPs) working in the primary care and community settings about the management of malnutrition and the prescription of oral nutritional supplements (ONS), often included in the treatment of malnutrition. Methods: Twelve healthcare professional (HCP) focus groups with 75 participants were conducted: community dietitians (n = 17), registered dietitians working in industry (n = 5), community and residential care nurses (n = 22), physiotherapists (n = 12), pharmacists (n = 9), occupational therapists (n = 6) and speech and language therapists (n = 4). Focus group discussions were audio-recorded and transcribed verbatim. The data were coded and analysed using thematic analysis and key themes with illustrative quotes extracted are presented. Results: Similar views on malnutrition management existed across professions. 'Gaps in Primary Care Management' was the first key theme wherein HCPs identified limitations in malnutrition management in the community. Barriers included limited or no dietetic services available in primary care and poor communication between general practitioners and wider primary care team members which resulted in inappropriate or delayed treatment. The second key theme, 'Challenges with ONS use in the Community', encapsulated several issues HCPs experienced with ONS usage including inappropriate prescribing and lack of monitoring of treatment goals. Conflicts of interest regarding dietitians working in industry assessing and treating older adults in residential care settings was highlighted by participants. Conclusions: This study highlights that more emphasis is needed to identify patients when they are at risk of malnutrition to avoid advanced or severe malnutrition presentations currently seen. Community dietitians for older people are required to address many of the issues raised including the need for awareness, education and training, resources, and malnutrition care pathway structures.